THE IMPORTANCE OF CLINICAL-BIOMETRIC, RADIOLOGICAL, AND EXPERIMENTAL STUDIES FOR OPTIMIZING COMPLEX ORTHODONTIC TREATMENT OF DENTAL AND MAXILLOFACIAL ANOMALIES (BASED ON LITERATURE SOURCES)). - Dilfuza Rakhmanova; Gavkhar Aripova; Shakhnoza Rasulova; Elbek Nasimov (Utilitas Mathematica, 2025)
Success in the treatment of dentofacial anomalies is mainly depends on correct diagnostics. In diagnostics and treatment planning, in prophylaxis of secondary deformation a big attention is paid to clinical data, biometric research, craniofacial studies of lateral cephalometries, analysis of soft tissues. One of the important factors to reach an optimal result is a decision of the anchorage. In case of extraction orthodontic treatment compete, approach is reached in the environment where the alveolar bone volume is maintained by applying biocompatible bone materials. Literature analysis showed that orthodontic treatment planning of dentofacial anomalies with extraction of different teeth is important and requires further research.